Techniques in Translating Terms of Service in the Go-Jek Application - Sukmaningrum, Rahmawati -; Herawati, Alvionita -; Setyaji, Arso - (Universitas PGRI Madiun, 2024)
In the age of digital platforms, in which Indonesia is seeing an increase, consumers may access a broader range of services, information, and en tertainment more easily. A platform called Go-Jek provides several services. One of the various menus in Go-Jek is the Terms of Service. It has Indonesian and English languages. When a translator translates a text, the meaning or message of the original language has to be accurately and successfully conveyed in the target language to enable translators to grasp a wide range of cultural backgrounds and consider grammatical structures. This study aims to clarify and determine the dominant technique for translating the terms of service in the Gojek. In order to complete missing words or phrases between the originating language to the targeted language, the translator’s responsibility is to provide accurate and creative ability. This study method is descriptive and qualitative and uses the translation theory of Molina and Albir (2002)—the data obtained by documents. A total of ten translation techniques were used in this translation. The top two are established equivalent techniques with 256 data frequency and literal translation with 107 data frequency. The dominant translation technique is the established equivalent technique. This indicates a stronger inclination toward the target language form in the translation.